Esej o Rozważności Ziemi Constantina Brâncuşiego - Noica, Constantin (Przestrzenie Teorii, 2019)
Constantin Noica treated Brâncuşi’s sculpture “The Wisdom of the Earth” (Cuminţenia pământului) in the same way he did “Endless Column”, as an artistic expression of the ontological vision characteristic of the Romanian sense of being. It brings together two great philosophical categories, traditionally seen as mutually exclusive: static being and dynamic becoming. Noica proves that Brâncuşi’s sculpture is unique in the way it illustrates “becoming into being” (Romanian = Devenirea întru fiinţa), the fundamental term in Noica’s ontology. Przełożył Andrzej Zawadzki.